Memórias em trânsito: confrontos entre lembrança e memória nos ambientes propostos pelos Centros de Memória e Cultura na Zona Leste do município de São Paulo - Santos, Regina Tavares de Menezes dos (2015)
This study epistemological objective is the communicational dimension of memory. From its empirical perspective, it was developed as a case study related to São Paulo city Zona Leste, considering its urging need for the conception of physical environments directed to the evocation and storage of memory. Our empirical targets were, therefore, the Centro de Comunicação e Educação Popular de São Miguel Paulista and the Centro de Memória e Cultura da Zona Leste. It was launched the following research inquiring: to what extend is there a relation between the recollection maintenance in spaces dedicated to memory and the process of building up individual and colective memory? Our hypothesis establishes that architectural and cultural heritages are impacted by the media influence in relation to their conception as communicative vehicles necessary to the evocation and storage of memory as well as towards the construction of memory communicative links based on a defined community experiences. Our general objective in this research is to understand how the effort to interchange memory to physical spaces deals with communication in its interactive and media dimensions, whereas its specific aims are: the establishement of considerations about communication and media environments developed in order to past portrayal; and the understanding between recollection and memory. This qualitative research is, therefore, based on study cases and field research, both using documental and bibliographical sources, as well as evidentiary method. Its theoretical basis about memory are found in the works of Jeudy (1990), Benjamin (1994), Bergson (1999) Huyssen (2000), Halbwachs (2004), Rossi (2010) and Dosse (2013). Concerning the distinctions between memory and recolletion, we make use of Lazzarato´s (2006), Tarde´s (2007) and Didi-Huberman´s (2013) studies. We also add to our considerations related to heritage concept the debates proposed by Meneses (1998), Harvey (2000), Ferrara (2002) and so. Concerning the debates about mediatization, interactions, fictionalization and identity, there are, respectively, the works of Braga (2008); Braga (2012); Augé (1998) and Bhabha (2013). In such authors we look for their understanding of memory using a critical perspective, as an object made invisible by historiography, and, therefore, the remains, the nighmares, the ghosts, the residual images, the silence